News on corruption and sociability networks: an exploratory study about Portugal, Brazil and Angola - Cunha,Isabel Ferin (2018)
The exploratory study we present is the result of the analysis of five news reports on corruption cases in Portugal and Brazil, with developments in Angola, a Portuguese speaking African country. The journalistic coverage and the mediatization of this issue were investigated in a project developed in Portugal and Brazil between 2012 and 2015. In this paper, we aim to analyze: how the networks of sociability are described in the texts and accompanying infographics; how the relationships between institutions and actors of the Lusophone space are presented in the news and in its infographics; the articulation between news coverage and infographics (Gray, Chambers and Bounegru, 2012); and infographics as devices for the mediatization of corruption and politics (Stromback, 2008; Hepp, 2012). Portugal, Brazil and Angola integrate the Lusophone space, a regional space within globalization, with historical roots in the Portuguese colonial empire, characterized by the sharing of a common language and by cultural proximity (Straubhaar, 1991; Davis, Straubhaar, Cunha, 2016).